2022
DOI: 10.1093/labmed/lmac017
|View full text |Cite
|
Sign up to set email alerts
|

Modified Proline Metabolism and Prolidase Enzyme in COVID-19

Abstract: Objective The aim of the study was to evaluate proline metabolism in patients affected by COVID-19. Materials and Methods This case-control study consisted of 116 patients with COVID-19 and 46 healthy individuals. Tests related to proline metabolism (prolidase, proline, hydroxyproline, glutamic acid, manganese) and copper and zinc tests were analyzed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…In agreement with findings from other studies [ 1 , 2 , 79 81 ], we detected decreased proline levels in those patients with severe COVID-19 studies. In this vein, it has been shown that decreased proline levels are associated with an unfavorable prognosis in patients with the severe form of this disease [ 80 , 82 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with findings from other studies [ 1 , 2 , 79 81 ], we detected decreased proline levels in those patients with severe COVID-19 studies. In this vein, it has been shown that decreased proline levels are associated with an unfavorable prognosis in patients with the severe form of this disease [ 80 , 82 ].…”
Section: Discussionsupporting
confidence: 93%
“…Then the "leave-oneout" sensitivity analyses used I 2 > 50% as the criterion to evaluate the robustness of conclusion of ferritin. Twelve studies [8,38,47,48,51,55,[57][58][59][60]62] on mortality (Figure 12) and four [17,20,21,24] studies on risk (Figure 13) were found to be the main reasons for the high heterogeneity. After excluding these studies, low heterogeneity and robust results without the small-study effect were demonstrated for mortality (SMD = 0; Z = 7.47; p < 0.001; I 2 = 44.2%) and risk (SMD = 0; Z = 7.39; p < 0.001; I 2 = 44.8%) analyses of ferritin.…”
Section: Sources Of Heterogeneity and Publication Biasmentioning
confidence: 99%
“…Figure 13. Galbraith plot for the contribution of results from the different studies [10,[17][18][19][20][21]24,36,37,[42][43][44]72] about risk for ferritin to the heterogeneity. This analysis was based on the relevant data listed in Table1 and the number orders in the plot were same to the reference list.…”
Section: Sources Of Heterogeneity and Publication Biasmentioning
confidence: 99%
See 2 more Smart Citations